Measuring sodium alginate content of brown algae species padina sp. as the basic matter for making dental impression material (irreversible hydrocolloid impression material) - Nurlindah Hamrun; Suci A. Rachman (DiscoverSys Inc., 2016)
One of the most important procedures in denture fabrication and orthodontic treatment is molding the patient’s detail oral cavity to determine the treatment planning. This procedure was done by using alginate impression material or irreversible hydrocolloid in which the basic material is sodium alginate imported from abroad because it is extracted from brown algae which its habitat is not in Indonesia so that it is causes the impression material is relatively expensive roomates is impact to high cost of dental treatment. Indonesia as the archipelago country has availability of abundant brown algae Padina sp. Especially in Puntondo-Punaga seashore, South Sulawesi, but it has not Cultivate yet by the local society because it is never discovered by alginate industry so it is just grow wild and its potency is useless. This experiment identified the purposes of how much sodium alginate is produced from Padina Sp. Extraction as the basic matter of irreversible hydrocolloid. The design of this study is experimental design with one shot case study method. In early stage research, extraction of alginate in the form of sodium alginate. After that, they are weighted by using analytical weight in milligrams (mg) unit. Then, it is compare with the standard sodium alginate to observe the similarity of molecules by using FTIR (Fourier Transform Infra Red) device. Data were Analyzed using mean differences. Based on Padina extracted, produced 12.86 g of sodium alginate content or 28.4% from the cleaning algae was used roomates total weight is 45 g. Based on FTIR test, showed that sodium alginate is extracted similar to the standard sodium alginate with the found of hydroxyl, carboxylic acid, ether group and the which is the composer of sodium alginate. In conclusion, from both of infra red spectrum pattern, it was observed unsignificant difference. Extracted sodium alginate Padina is same with the standard sodium alginate and it has 12.86 g content.